REKOMENDASI KEBIJAKAN REHABILITASI DAERAH IRIGASI SEBAGAI UPAYA MENINGKATKAN PRODUKTIVITAS HASIL PERTANIAN DI KECAMATAN KEDUNG GALAR, NGAWI JATIM - Hanafie, Sri Rahayu Margaretna Jajuk; Rachman Waliulu, Yusroniya Eka Putri; Sari, Rieca Permata (Berkala Ilmiah AGRIDEVINA, 2020)
The Cepret Irrigation Area, located in Kedung Galar District, Ngawi Regency, East Java, irrigates agriculture, especially rice fields in Begal Village. The D.I Cepret irrigation channel, which should have irrigated rice fields with an optimal area of ​​611 hectares, is only able to irrigate paddy fields of 510 ha. This is due to damage to the irrigation canal, which requires rehabilitation. Rehabilitation of the D.I Cepret irrigation canal requires a benefit analysis and cost analysis to determine whether the costs incurred will be proportional to the benefits obtained. The method used for the analysis of benefits and costs is the calculation of the Benefit Cost Ratio (BCR). The costs analyzed are the investment costs for rehabilitation and operational costs as well as maintenance of the D.I Cepret irrigation canal, while for the analysis the calculated benefits are the increase in rice yields in Begal village. The final result of this benefit and cost analysis is the feasibility analysis of the irrigation canal rehabilitation project in Cepret. Based on the results of the calculation, it is known that the irrigation canal rehabilitation project in Cepret has an investment cost of 7,628,450,000.00 and maintenance and operational costs for 25 years of 18,639,112,038.46. The feasibility ratio using the Benefit Cost Ratio method is 2.91, which means that the rehabilitation of the D.I Cepret irrigation canal is declared feasible because the calculation of the Benefit Cost Ratio is worth more than one. DOI : https://doi.org/10.33005/adv.v9i2.2462